3D topology optimisation of liquid-cooled microchannel heat sinks. (1st August 2022) - Marshall, Samuel D.; Lee, Poh Seng
Highlights: Thorough numerical analysis of novel method for designing heat sink geometries. Full 3D topology optimisation outperforms equivalent 2D topology optimisation. Enhancement likely due to improved vertical and spanwise mixing within channel. Smoothing and simplification of the heat sink design are performed and discussed. Results useful for industrial/academic developers of heat sinks via AM techniques. Abstract: A full 3D topology optimisation is conducted in COMSOL to develop fin structures for a heat sink. Nine topologies are generated, and then imported into FLUENT for numerical testing. To permit fabrication, the geometries were smoothed, and then tested again. The geometry with the highest performance in terms of bottom temperature and pumping power was extended from 15 mm to 45 mm via a linear repeating pattern, shown to be superior to simply stretching the design. The final design was then compared with a 2D geometry that had been generated by an equivalent topology optimisation, with the 3D geometry found to have higher heat transfer efficiency. In this way, the advantages of 3D topology optimisation are demonstrated. A detailed study of the temperature and velocity flow structure in FLUENT suggests that this enhancement is due to improved vertical and spanwise mixing within the channel. The fins of the 3D topology act to force the cold regions of the fluid to interact with the heated surface, thus improving thermal transfer. A simplified version of the 3D geometry confirms that the major fin structures cause the majority of this effect. As such, these results have relevance for future designers of effective heat sinks.